Há possibilidades de uma psicologia libertadora na contemporaneidade? - Silva, Antonio Carlos Barbosa da [UNESP]; Casadei, Marina Coimbra [UNESP] (My University, 2011)
This article aims to generate reflections on the current Brazilian educational situation and briefly discuss the changing paradigms of post-modernity that affect it. Today's education will be discussed and questioned from the mold of traditional education institution (postulated analyzed and criticized by Paulo Freire and still present in our society) and soon to be opposed to the proposal from liberating pedagogy (teaching theoretical foundations that focus on developing of a social nature of no alienation and contribution to the formation of critical subjects of their own destiny, comes in trying to transform the current education, reinforced by the individualistic and consumerist bonds in a democratic education (teachers and students in a relationship horizontal) facing the current questions of social values.

Este artigo tem por objetivo suscitar reflexões acerca da situação educacional brasileira vigente e discutir brevemente as mudanças de paradigmas da pós-modernidade que a afeta. A educação atual será debatida e questionada a partir dos moldes da educação tradicional bancária (postulado analisado e criticado por Paulo Freire e ainda presente em nossa sociedade) e logo em seguida será contraponteada com a proposta da pedagogia libertadora (fundamentos teóricos pedagógicos que visam o desenvolvimento de um caráter social de desalienação, enquanto contribuição para a formação de sujeitos críticos de sua própria história) enquanto uma força contrativa dos liames alienadores da educação bancária e favorável a uma educação democrática (formação ativa que coloca educadores e educandos numa relação horizontal) voltada para os questionamentos dos valores sociais contemporâneos.